Surgical education using a multi‐viewpoint and multi‐layer three‐dimensional atlas of surgical anatomy (with video). (15th April 2014) - Nobuoka, Daisuke; Fuji, Tomokazu; Yoshida, Kazuhiro; Takagi, Kosei; Kuise, Takashi; Utsumi, Masashi; Yoshida, Ryuichi; Umeda, Yuzo; Shinoura, Susumu; Takeda, Yoshimasa; Ohtsuka, Aiji
Abstract Background Trainee surgeons must have a good understanding of surgical anatomy. Especially in the hepatobiliary‐pancreatic field, beginning surgeons often find it difficult to recognize the three‐dimensional structure of the target organ and its complex anatomical correlation with surrounding organs. Conventional anatomy textbooks are not written with the aim of teaching these three‐dimensional structures and complex correlations. We developed a novel teaching atlas of surgical anatomy using a multi‐viewpoint and multi‐layer three‐dimensional camera system. Methods Layer‐by‐layer dissection of the upper abdominal organs of a cadaver was performed by expert surgeons. A stereoscopic camera system was used to capture a series of anatomical views. The images were remodeled in a multi‐viewpoint and multi‐layer manner. Results Images of each dissection layer could be viewed serially from the appropriate angle, which was tilted up to 90° along the anteroposterior axis. The clinical anatomy specific to the surgical procedure could thus be learned using this atlas system. Conclusions Rotatable three‐dimensional panoramic views of local dissection of the upper abdominal organs of a cadaver were developed for educational purposes. Trainee surgeons could use these anatomical images instead of conventional anatomical atlases to learn how to perform surgical procedures such as pancreaticoduodenectomy and major hepatectomy.